Study on the Potential Utilization of Used Cooking Oil as an Alternative Substitute for Transformer Oil - Warindi D; Haru Wicaksono; Wahyudi Budi Pramono (Depertment of Electrical Engineering University of Mataram, 2023)
The widespread use of bulk cooking oil in Indonesian households has led to an increase in used cooking oil waste, particularly from eel frying, which can have adverse environmental effects. This study aims to explore the potential of using used cooking oil as a more sustainable alternative to transformer insulation oil (DIALA-B). Previous research has investigated the impact of contaminants such as carbon and water on the breakdown voltage of transformer oil. Methods involving heating, magnetization, and filtration have been employed to improve the quality of used transformer oil. This study follows a similar approach, examining the characteristics of used cooking oil from eel frying and its filtration process using filter paper, while considering factors such as water content, copper strip corrosion, and kinematic viscosity. The research focuses on understanding the characteristics of used cooking oil as a DIALA-B substitute in transformer insulation, enhancing its insulation properties through filtration, and analyzing water content, copper strip corrosion, and kinematic viscosity. Treatment involving heating and filtration has been found to increase the breakdown voltage of used cooking oil, while reusing the oil can decrease its breakdown voltage. Overall, used cooking oil from eel frying exhibits suitable kinematic viscosity and low corrosion levels but has relatively high water content. Reducing the water content through appropriate treatments can improve its breakdown voltage.